Bloqueio pericoal guiado por ultrassom: ensaio clínico randonizado - Najman, Ilana Esquenazi [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Background and Goal of study: Periconal anesthesia has long been the choice technique for ophthalmic surgery. Currently, there is limited published data on ultrasound-guided ophthalmic anesthesia. Nevertheless, as in other areas of regional anesthesia, ultrasonography may contribute to improve the safety of ophthalmic blocks, particularly by reducing globe perforation or penetration incidence associated with the needle-based techniques. This study aimed to evaluate the benefits of the ultrasound-guided periconal block in comparison to the blind periconal technique with regard to the feasibility, positioning of the needle and occurrence of complications, in patients with healthy eyes. Methods: Upon the approval of the Institutional Ethics Committee, a prospective clinical study was carried out. One hundred and twenty-nine patients (ASA I-II) undergoing cataract surgery were randomly assigned to have their eyes anesthetized using either the Real-Time Ultrasound-Guided Periconal Blockade (USGblock, n=69) or the Conventional Periconal Blockade Technique (Cblock, n=60), followed by ultrasound examination of the eye. Patients with single eye and with high myopia (axial length greater than 26 mm) with the presence of staphyloma were excluded. The Chi-square and Fisher's exact tests were used for qualitative variables and the Student's t-test for quantitative variables. The significance level was 5%. Results: There was a higher incidence of unintentional intraconal needle placement (n=12) in Cblock than in USGblock (n=1) (P<0.0001). The distance between the needle tip and the optic nerve was 12.1±4.4 mm (mean±SD) in USGblock and 8.2±3.7 mm in Cblock (P<0.0001). Needle insertion depth was 25.1±1.6 mm in USGblock and 26.7±2.4 mm in Cblock (P<0.0001). Needle length displayed in the ultrasound image was 11.7±2.6 mm in USGblock and 14.7±3.5 mm in Cblock (P<0.0001). Only one patient presented with conjunctival edema (chemosis). No further ...

Justificativa e Objetivos: O bloqueio periconal é uma técnica anestésica muito utilizada em cirurgias oftalmológicas. Atualmente, existem poucos relatos na literatura sobre a anestesia oftalmológica guiada por ultrassom (US). No entanto, assim como em outras áreas da anestesia regional, o ultrassom pode contribuir para melhorar a segurança dos bloqueios oftalmológicos, particularmente pela redução da incidência de perfuração ou penetração ocular associada aos bloqueios oftalmológicos que introduzem a agulha às cegas. Com isso, o presente estudo visou avaliar a viabilidade do ultrassom como guia na realização do bloqueio periconal, assim como a identificação do real posicionamento da agulha na cavidade orbitária e a ocorrência de complicações em comparação com a técnica às cegas em pacientes com olhos sem patologias. Métodos: Após a aprovação do Comitê de Ética em Pesquisa, um ensaio clínico prospectivo randomizado foi realizado. Assim, 129 pacientes (ASA I-II) foram alocados de forma aleatória entre os grupos Bloqueio Periconal Guiado por Ultrassom (Grupo USG, n=69) e Bloqueio Periconal Convencional com confirmação posterior do posicionamento da agulha, pelo ultrassom (Grupo C, n=60). Pacientes com olho único e pacientes alto míopes (comprimento axial > 26 mm), com a presença de estafiloma foram excluídos do estudo. Os testes, qui-quadrado ou o teste Exato de Fisher, foram usados para análise das variáveis qualitativas; já o teste t de Student foi usado para análise das variáveis quantitativas. O nível de significância do estudo foi de 5%. Resultados: Houve uma maior incidência de posicionamento da agulha intraconal não intencional (n=12) no Grupo C em relação ao Grupo USG (n=1) (P<0,0001). A distância entre a ponta da agulha e o nervo óptico foi de 12,1±4,4 mm (média±DP) no Grupo USG e 8,2±3,7 mm no Grupo C (P<0,0001). Já, a profundidade de inserção da agulha foi ...
Ultrasound guided periconal blockade: randomized clinica trial
Keywords: Anestesia em oftalmologia; Olhos - Cirurgia; Anestesia local; Ultrassom; Local anesthesia; Anesthesia in ophthalmology